Activity Based Costing: A Tool To Aid Decision Making In Pharmaceutical Firms (Journal of Pharmaceutical Negative Results, 2022)
This study aims to determine the application of activity based costing in the decision making of pharmaceutical companies in Deli Serdang in determining which products will be a top priority for mass production. A descriptive approach is applied in this study through a collection of previous literature on activity based costing in making decisions in producing an item. This study will provide a theoretical description of a method to assist decision making in pharmaceutical companies using activity based costing. Therefore, the methodology used is interviews, surveys and pure literature and conclusions are drawn from theoretical analysis and discussion results. This research will add insight into management accounting, especially activity based costing. Based on the determination of production prices using activity based costing, it results that the manufacture of product B results in a unit price for each product produced which is more expensive than product A. This is the basis for PT. XXY to be able to determine which products are better produced. The cost per unit for product A is Rp.8,506 while for product B is Rp.10,535. Taking this into account, the production costs are 19 - 20% lower after calculations are carried out using the activity based costing method. Researchers try to convey matters relating to the production carried out to the company. So that the basis for making decisions in determining the production of one of the two products that the company chooses will make it easier for the parties involved who produce drugs.